Determination of the Grain Boundary Facets Orientation in New Recrystallized Grains; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Kondrateva N. S. (2018, 2018)
Title screen